(untitled) (Baltimore, 1972)
Book covers a wide range of subjects including transport, industry, population trends, water resources, regional Britain and Europe, and speculations on the future society
Keywords: Natural resources,Tài nguyên thiên nhiên; Great Britain,Nước Anh